Pan-Islamisme Dan Pengaruhnya Pada Pendidikan Di Indonesia - Khafidz Al Khaq, Abdullah; Syafiqul Humam, Muhamad; Murniati, Tri (Ar-Rusyd: Jurnal Pendidikan Agama Islam, 2024)
This article explores the influence of Pan-Islamism on the education system in Indonesia, including its ideological, historical, and curriculum impacts in the modern era. Using a qualitative library research method, this study examines the transformative role of Pan-Islamism, inspired by figures like Jamaluddin al-Afghani and Muhammad Abduh, in shaping Islamic education through organizations such as Jami'at al-Khair, Al-Irsyad, Sarekat Islam, Muhammadiyah, and Nahdlatul Ulama. The findings reveal that Pan-Islamism has modernized curricula by integrating general science with Islamic values, fostering a generation of Muslims who can navigate modern challenges while adhering to Islamic principles. Thus, this research provides significant insights into the relevance of Pan-Islamism in shaping Indonesia's education system.